(untitled) (Research, Society and Development, 2023)
Urinary tract infection (UTI) is one of the most frequent infections that affect patients in hospitals and can be classified as cystitis or pyelonephritis, depending on the site of infection. The diagnosis of UTI is basically made by performing the urine summary (EAS) and urine culture. Thus, the objective of this study was to conduct a retrospective study from January/2021 to December/2021 based on the database of the clinical analysis laboratory of the University Hospital Lauro Wanderley (HULW) in the state of Paraiba in relation to the alterations presented in the EAS exam, mainly with the markers nitrite and leukocyte esterase from positive urine cultures. The epidemiological data of these infections was also observed, as well as their bacterial incidence. A total of 1817 urine cultures were obtained, of which 837 had a request for EAS concomitantly, and of these 129 urine culture samples were positive, with the prevalent microorganisms being Escherichia coli (36.5%), Klebsiella pneumoniae (20.6 %) and Pseudomonas aeruginosa (8.7%). Nitrite was observed in 16% of the samples and leukocyte esterase in 58%. We conclude that regarding the results of the EAS, leukocyturia proved to be a more sensitive marker to aid in the diagnosis of UTI compared to nitrite, corroborating the specialized scientific literature, with a predominance of UTI in female patients.